The Effect of Helicobacter pylori Infection on Overweight: A Systematic Review and Meta-Analysis - Farideh Kamarehei; Younes Mohammadi (Tehran University of Medical Sciences, 2022)
Background: The association between Helicobacter pylori infection and overweight, as one of the most common health issues, remains controversial. In this study, we systematically reviewed the effect of H. pylori infection and overweight to get a reliable answer. Methods: We used the Preferred Reporting Items for the Systematic Review and Meta-Analysis statement. We searched the association between H. pylori and overweight infection in international databases including Medline, Web of knowledge and Scopus, without any limitations of language, publication type, and publication status in search step of this systematic review from 2000 to 2020. We surveyed the title, abstract and full text of each research studies, and we used Newcastle-Ottawa quality for assessing the quality of each paper. A random effects model was used to calculate the pooled odd ratio with 95% confidence intervals. Results: Fifteen papers were eligible for this review. The selected studies reported different Odd Ratio between overweight and H. pylori infection but Odds Ratio (95% confidence interval) in our systematic and meta-analysis study was estimated at 1.42 (95%CI; 1.12, 1.81) and it was statistically significant (P: 0.003). Conclusion: H. pylori infection is significantly associated with overweight, therefore, the eradication of H. pylori infection is suggested because this infectious might be resulted in overweight.